High-efficiency multi-crystalline black silicon solar cells achieved by additive assisted Ag-MACE. (1st January 2020) - Li, Xinpu; Gao, Zhibo; Zhang, Danni; Tao, Ke; Jia, Rui; Jiang, Shuai; Wang, Bolong; Ji, Zhuoyu; Jin, Zhi; Liu, Xinyu
Graphical abstract: An additive was developed in Ag-MACE process to prepare black silicon with uniform texturing, as a result, both the appearance and output-performance of solar cells were improved. Highlights: An additive was adopted to control the etching rate of crystallites with different orientation. The crystal boundaries of polysilicon black cells are very blurry. An efficiency of 19.56% was achieved for multi-crystalline black silicon solar cells. Abstract: It is important for uniform texture on crystallites with different orientation of diamond wire sawn multi-crystalline silicon solar cells by Ag metal-assisted chemical etching method (Ag-MACE). In this paper, an additive was adopted to make the nanostructures on crystallites with different orientation of multi-crystalline silicon wafers with roughly the same depth and diameter. This additive contains biological enzymes, which are macromolecular proteins with specific catalytic functions. The uniform texture produced by the additive is demonstrated to be helpful in improving the cell performance in terms of surface morphology, reflectivity, effective minority carrier lifetime, auger recombination rate, internal quantum efficiency and external quantum efficiency measurements as well as electroluminescence spectra characterizations. The chemical mechanism of additive assisted etching reaction during the texturing process was discussed. Finally, mass-produced multi-crystalline silicon solar cells made by Ag-MACE with the additive achieve a maximum efficiency and average efficiency of 19.56%, and 19.24%, respectively, which were 0.65% and 0.64% absolutely higher than that without the additive. Moreover, the effective minority carrier lifetime and auger recombination rate of the former was nearly twice and a third of that of the latter respectively.